IMPLEMENTASI DAN PENGUJIAN STRUKTUR DATA BERBASIS ACUAN UNTUK PROGRAM APLIKASI MENGUNGKAP KEPRIBADIAN BERDASARKAN TANGGAL LAHIR DAN NAMA - SM Santi Winarsih; Agus Winarno Wahono (STMIK Sinar Nusantara, 2022)
ABSTRACTThe depth of IF (IF_Then_Else) structure of an algorithm influence the execution speed of program. One of the way to speed up the execution of program is reducing the depth of the existing IF structure or reduce the number of selections (IF) in an algorithm process. The idea based on this research is to reduce the IF structure (IF Then Else) smaller then IF structure, through a concept of transforming the IF structure (IF_Then_Else) into a reference structure. This method is doing by mapping the criteria in the selection into a reference index. The process of transforming the IF structure into a reference structure becomes the concept of designing a data structure into the topic of this research. This research is continuinng from the previous research which is the purpose of this research is implementing and testing the reference based on the data structure for the application program to express personality based on date of birth and name . The concept hopefully be able to carry out the program fastly. The steps of this research are starting with the literature study step to find out the references then collecting the data, identifying and classifying the data and arranging into correct pattern, then decide the steps to access the data and finally continuing the implementation and testing of the system. The reference data structure, the selection process (IF THEN ELSE) can be eliminated, because the process of fulfilling the selection criteria can be replaced with a reference. Beside of the implementation process and system testing, the output of this research will plan to articles in scientific journals and registered with HKI.